Accommodements, contournements et preuves identitaires : réflexions sur quelques stratégies individuelles déployées devant la commission de classement des récidivistes pour échapper au bagne (fin XIXe-début XXe siècle) - Jean-Lucien Sanchez (Criminocorpus)
Before they left for the prison, the relégués could address requests to a commission of classification of the recidivists who met shortly before the organization of a convoy. If the remedy appeared to be legitimate, it could order further inquiries and, if necessary, submit a proposal of pardon to the Criminal Affairs and Pardons Department of the Department of Justice. Many relégués tried to lie about their identity to deceive the members of the commission. But they managed to easily circumvent these strategies through the use of identification tools such as the criminal record or anthropometry.